Manuskrip dan Konteks Sosialnya, Kasus Naskah Tarekat Naqsyabandiyah di Minangkabau - Masmedia Pinem (Jurnal Lektur Keagamaan, 2012)
This paper discusses Tarekat Naqsyabandiyah (manuscript on the Naqsyabandiyah Sufi order) in Minangkabau, West Sumatera. In addition to describe the physical aspect of the manuscript, this paper discusses the contents of the manuscript concerning the doctrines of Sufism, such as the method of ©ikr (remembering God’s name with chanting special formula), tawhīd (Islamic monotheism) and the relationship between syari‘ah, tarekat, hakikat and makrifat. The paper also discusses social, cultural and religious aspects of the manuscript. In this context, the author shows rivalry between the Naqsyabandiyah and Syattariyah sufi orders, when the former criticized the latter on the doctrine of the martabat tujuh (seven stages).